If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 7 = 7c + 52 Reorder the terms: 7 + 2c = 7c + 52 Reorder the terms: 7 + 2c = 52 + 7c Solving 7 + 2c = 52 + 7c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-7c' to each side of the equation. 7 + 2c + -7c = 52 + 7c + -7c Combine like terms: 2c + -7c = -5c 7 + -5c = 52 + 7c + -7c Combine like terms: 7c + -7c = 0 7 + -5c = 52 + 0 7 + -5c = 52 Add '-7' to each side of the equation. 7 + -7 + -5c = 52 + -7 Combine like terms: 7 + -7 = 0 0 + -5c = 52 + -7 -5c = 52 + -7 Combine like terms: 52 + -7 = 45 -5c = 45 Divide each side by '-5'. c = -9 Simplifying c = -9
| 3-8y=-1 | | x-7y+y-3-2x+6z= | | (3x-3y)2+18xy= | | 1.15=(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x) | | 4x/3+=2 | | -2x+6=-7x+14 | | 4(3x-2)-5(2-x)= | | 17.01y=6.3 | | 9a-6(a+5)= | | .2*n=48 | | (X/4)+3=5 | | 5p-2=9p-2 | | 14c-6=7c-6 | | 10f+4=3f-59 | | 12x-(x*x)=36 | | 3(2a-3b)-4b(4a-4)= | | Z^2+6z-20=00 | | -6w-45=-9(w+8) | | 9x-5y=12 | | Z^2+6x-16=0 | | 50x^2+15x-2=(5x+2) | | 4p-1=9+17 | | 6x-10=6+10 | | 9q+1=4q-44 | | 2=3c+11 | | 4x+40=12x-102 | | (3/2)+4=5 | | x(8+9)= | | 3x/4-3.2=5.3-2x/3 | | 17b=36+3b | | -3c-32=4c+3 | | 5cos^2x-3=0 |